Intervention of Uncaria and Its Components on Liver Lipid Metabolism in Spontaneously Hypertensive Rats - Tian, Zhenhua; Zhang, Shiming; Wang, Huanjuan; Chen, Zhenshan; Sun, Mengjia; Sun, Linlin; Gong, Lili; Li, Yunlun; Jiang, Haiqiang (Frontiers in Pharmacology, 2020)
Uncaria rhynchophylla (Miq.) Miq. ex Havil is widely used in the treatment of hypertension. The Uncaria extract, and its bioactives, rhynchophylline and isorhynchophylline; reduced the blood pressure and fatty content in liver cells. In present study, the anti-hypertensive effects of Uncaria ethanol extract (UET), rhynchophylline (RT) and isorhynchophylline (IT) were investigated in spontaneously hypertensive rats (SHR) using UPLC-Q-Orbitrap/MS based lipidomics approach . Histological changes in liver were evaluated. Cytolysis and fatty degeneration in liver tissues were observed in SHR group. Lipid species in WKY, SHR treated with UET, RT and IT were plotted to obtain the Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) score plots. Fifty-six endogenous metabolites in liver such as glycerides, glycerophospholipids, unsaturated fatty acids and sphingomyelins were selected as potential hypertension associated biomarkers. In order to further explore the metabolite targets of UET for antihypertensive, student’s t test, and correlation analysis were performed to recognize the pattern recognition and to select the significant metabolites. Similar and prolonged reduction in blood pressure was observed in all SHR groups treated with UET, RT and IT, while the metabolite profiles were perturbed slightly compared to that of untreated SHR. Further analysis showed that only a few common components were observed in both RT and IT, which showed the similar antihypertensive effect in spite of the distinct metabolic pathways. These results help in understanding the mechanisms of isomeric ingredients in exhibiting the antihypertensive effect but with different targets.